Slow-release fertilizer on the seedling growth of Aspidosperma parvifolium A. DC. - Menegatti, Renata Diane; Guollo, Karina; Navroski, Márcio Carlos; Vargas, Oieler Felipe (Scientia Agraria Paranaensis, 2017)
The aim of this study was evaluate the use of different fertilizer doses of controlled release in the production of Aspidosperma parvifolium A. DC. The seedlings were originated from seeds, sown in plastic bags of 500 cm3 and filled with substrate Tecnomax®. The design was completely randomized with four treatments, consisting of four increasing doses (0.0; 2.5; 5.0 and 7.5 g L-1) of Osmocote® fertilizer. For each treatment were used five replications with four plants each. After 150 days of emergence were evaluated the diameter of the neck, total seedling height, number of leaves per seedling, and leaf area. It was found that plants belonging to treatments with the use of slow release fertilizer, particularly those subjected to 5.0 g L-1 responded similarly, resulting in better quality seedlings. The slow-release fertilizer levels influenced the early growth seedlings, indicating the potential use of this fertilizer in the production of Aspidosperma parvifolium seedlings.